Investigation on the heat transfer and evolution of temperature gradient through wood during drying; Case study: beech (Fagus orientalis) and spruce (Picea abies) - asghar tarmian (Regional Information Center for Science and Technology (RICeST), 2010)
The heat transfer through three orthotropic directions and the evolution of temperature gradient in beech (Fagus orientalis) and spruce (Picea abies) during drying were investigated. Thus, due to low capacity of dryer, small flat-sawn boards with dimensions of 80 × 25 × 40 mm (L×R×T) were used. Then, the boards were dried at the dry-bulb temperature of 60 °C and relative humidity of 50 %. Four surfaces of the boards were coated by polyurethane-coated aluminum foil to confine the heat flux along one direction. Then, the boards were thermally insulated by 50 mm-thick Styrofoam. Some holes with 1mm in diameter were made on the board specific distances to measure the temperature using thermocouple. The results showed that the temperature of each wood increased as heating up progressed until it reached to the wet-bulb temperature. Then, it remained at an almost constant value as the wet bulb temperature until the wood moisture content reached the hygroscopic range. Furthermore, the pattern of the temperature profile for both wood species was almost identical. The surface temperature of the boards increased until it reached the dry-bulb temperature of 60 °C, while the core temperate remained as the wet-bulb temperature (48-52 °C) throughout the rest of drying period.